The role of ANGPTL4 in cancer: A meta-analysis of observational studies and multi-omics investigation - Osama M. Younis; Abdalrahman S. Dhaydel; Wasfi F. Alghwyeen; Noor R. Abu Hantash; Leen M. Allan; Issam M. Qasem; Anwaar Saeed (PLoS ONE, 2025)
Background Angiopoietin-like protein 4 (ANGPTL4) plays a crucial role in processes such as angiogenesis, inflammation, and metabolism. Despite numerous studies suggesting its involvement in cancer, a definitive role remains unclear. We introduce the first comprehensive meta-analysis and pan-cancer bioinformatics study on ANGPTL4, aiming to unravel its implications across various cancer types. Methods Moderate-to high-quality observational studies were retrieved from PubMed, Scopus, and Embase. A meta-analysis was conducted using the R package “meta.” Survival analysis was performed using GEPIA2 and TIMER2.0. Immune infiltration, mutational burden, and drug resistance analyses was done via GSCAlite. Co-expression and gene set enrichment analyses (GSEA) were carried out using cBioportal and enrichr, respectively. Results Increased ANGPTL4 expression was linked to worse tumor grade (OR =  1.51, P = 0.023), stage (OR =  2.42, P < 0.001), lymph node metastasis (OR =  1.76, P = 0.012), vascular invasion (OR =  2.16, P = 0.01), and lymphatic invasion (OR =  2.20, P < 0.001). Furthermore, ANGPTL4 expression was linked to worse OS (HR = 1.40, 95% CI: 1.29,1.50, P = 0.0001). Single gene level analysis revealed that ANGPTL4 upregulated epithelial-to-mesenchymal transition (EMT) in 23 different cancers. Immune infiltration varied between cancer types, but increased infiltration of cancer-associated fibroblasts was observed in most cancers. Mutation analysis revealed increased alterations in TP53 and CDKN2A in cohorts with ANGPTL4 alterations. GSEA of co-expressed genes revealed involvement in hypoxia, EMT, VEGF-A complex, TGF-B pathways, and extracellular matrix organization. Conclusions ANGPTL4 plays a significant role in tumor progression via its positive regulation of EMT and angiogenesis, while possibly harboring a TGF-B dependent role in systemic metastasis. Therefore, ANGPTL4 is a suitable target for future drug development.